ERRATUM: A Method to Discriminate Between the Candida stellata and Saccharomyces cerevisiae in Mixed Fermentation on WLD and Lysine Agar Media - EDITOR, FROM (South African Journal of Enology and Viticulture, 2016)
Received from the authors of the following paper, published in 2011, volume 32(1), pp 35-41